Optimization of “Major Shoesclean” Shoe Care and Washing Services : Integrating Digital Platform Technology to Increase Promotional Effectiveness - Dimas Prayoga, Aditya Galuh; Suprayitno, Suprayitno; Wicaksono, Christian (Edumedia Solution, 2025)
This report presents the results of a community service initiative aimed atoptimizing the shoe care and cleaning services provided by Major Shoesclean, asmall and medium enterprise (SME) established in Klaten. With the growingawareness of the importance of shoe maintenance, Major Shoesclean faceschallenges in expanding its market reach and enhancing service quality. Toaddress these challenges, this initiative integrates digital technology intomarketing and service management processes.The methods employed include thedevelopment of a website, the introduction of Google Maps for betteraccessibility, and promotional activities conducted at the Ngarsopuro NightMarket. These strategies aim to enhance visibility and attract a broader customerbase.The outcomes of this initiative indicate significant improvements inoperational efficiency, customer satisfaction, and public awareness regarding theimportance of proper shoe care. The implementation of a computerizedinformation system allows for better data management and streamlined servicedelivery.Overall, this program is expected to have a positive impact on thegrowth of Major Shoesclean and contribute to the economic empowerment of thelocal community, fostering sustainable development within the SME sector.